Arctic Bibliography. Volume 15. - Martna, Maret H. (1971)
The present volume of Arctic Bibliography summarizes and indexes 8299 publications making a total of 101599 books and papers abstracted since the beginning of the project. Mineral exploration and development continues to be the most widespread and intensive interest in the North and is so reflected in the literature, with papers in the field of geology and mineralogy the most numerous of all. Transportation, a key factor in northern development, is so represented in the literature on air, and surface travel and freighting, and transportation by pipeline. Formation and growth of ice, its strength, impact on harbor installations, power stations, etc., are described. (Author) See also Volume 14, AD-696 641.